Perfectionism, Big Five and biopsychosocial functioning among parents of children with and without acquired brain injury (ABI). (7th June 2022) - Yehene, Einat; Zukerman, Hadas; Goldzweig, Gil; Gerner, Maya; Brezner, Amichai; Landa, Jana
ABSTRACT: Background and objective: Personality factors are often investigated in the context of parenting but are rarely studied in relation to coping with child disabilities like pediatric acquired brain injury (pABI). This study (1) compares Biopsychosocial functioning (BPSF), Big Five personality traits, and dimensions of perfectionism of parents of children with and without pABI, and (2) examines the role personality factors play in parental BPSF in each group. Method: 57 parents of children who sustained a significant pABI and 50 parents of typically developing children participated in this cross-sectional study. Parents completed scales measuring Multidimensional Perfectionism, Big Five inventory, and BPSF. Results: Among the pABI group, multivariate analysis indicated significantly poorer BPSF, higher levels of neuroticism, socially prescribed perfectionism, and lower levels of openness, than controls. Regression analysis showed that personality explained 60.5% of the variance in parental BPSF post pABI. In both samples, neuroticism and socially prescribed perfectionism appeared as two prominent personality factors with a significant negative effect on parental BPSF, while self-perfectionism appeared prominent only in the pABI group, indicating a significant positive effect. Implications: pABI may result in changes to parents` personality. Personality characteristics significantly contribute to parental BPSF post-injury and should be addressed in clinical practice.